The Germ Similarity in Ontogeny of Ciliates (Ciliophora) - Dovgal, I.V. (Вестник зоологии, 2002)
The paper deals with the regularities of ontogenesis of mobile and sessile ciliated protozoans. It is shown, that the germ similarity is characteristic both in mobile and sessile ciliates. The mechanisms of controlling of morphogenesis in ciliates are probably homologues with the controllers of early morphogenesis in multicellular organisms. The special statement for the case of law of germ similarity in unicellular eucaryots named "principle of tomits similarity" has been offered. В статье рассматриваются особенности онтогенеза подвижных и прикрепленных инфузорий. Показано, что зародышевое сходство проявляется как у подвижных, так и у сидячих форм. Механизмы регуляции онтогенеза у инфузорий и ранних этапов морфогенеза многоклеточных, вероятно, гомологичны. Предложена специальная формулировка закона зародышевого сходства для онтогенеза одноклеточных эукариот — принцип сходства томитов.